Integrating microbial 16S rRNA sequencing and non-targeted metabolomics to reveal sexual dimorphism of the chicken cecal microbiome and serum metabolome - Yang, Yongxian; Zhang, Fuping; Yu, Xuan; Wang, Liqi; Wang, Zhong (Frontiers in Microbiology, 2024)
The gut microbiome plays a key role in the formation of livestock and poultry traits via serum metabolites and empirical evidence has indicated these traits are sex-linked.We examined 106 chickens (54 male and 52 female) and analyzed cecal content samples and serum samples by 16S rRNA gene sequencing and non-targeted metabolomics, respectively.The cecal microbiome of female chickens was more stable and more complex than that of the males. Lactobacillus and Family XIII UCG-001 were enriched in males while Eubacterium_nodatum_group, Blautia, unclassified_Anaerovoraceae, Romboutsia, Lachnoclostridium and norank_Muribaculaceae were enriched in females. Thirty-seven and thirteen differential metabolites in positive and negative mode respectively were identified that differed by sex and sphingomyelin metabolites possessed the strongest association with cecal microbes and 11β-hydroxytestosterone was negatively correlated with Blautia. Conclusion: These results support the role of sexual dimorphism of the cecal microbiome and metabolome and implicate specific gender factors associated with production performance in chickens.